Pengaruh Kualitas Pelayanan dan Harga terhadap Keputusan Pembelian melalui Kepuasan Konsumen sebagai Variabel Intervening: Studi pada Toko Abadi Kecamatan Gadung Kabupaten Buol - Said, Miranti Ar; Darnawati; Puyo, Marten (Melati Institute, 2025)
Consumer purchasing decisions have made one of the most important aspects for companies, because they are considered a valuable asset. Important aspects related to purchasing decisions include service quality, price, and customer satisfaction. This study aims to determine and analyze the effect of service quality and price on purchasing decisions through customer satisfaction at Abadi Store, Gadung District, Buol Regency. The sample in this study were 150 respondents as customers who often make purchases at Toko Abadi, Gadung District, Buol Regency. Data analysis in this study used the path analysis method through PLS-SEM with Algorithm and Bootstrapping calculations with the SmartPLS 3.0 software program. The results of the research on the first hypothesis that service quality has a positive and significant effect on purchasing decisions. This is evidenced by a p-value of 0.020, a t-statistic of 2.069, and an influence coefficient of around 0.137. The second hypothesis is that price has a positive and significant effect on purchasing decisions. The results of proving this hypothesis show a coefficient value of 0.574, a t-statistic of 9.415, and a p-value of 0.000. The third hypothesis is that service quality has a positive and significant effect on customer satisfaction. This result is evidenced by a coefficient value of around 0.283, a t-statistic of 3.825, and a p-value of around 0.000. The fourth hypothesis that price has a positive and insignificant effect on customer satisfaction, this is evidenced by a coefficient value of 0.122, a t-statistic of 1.461, and a p-value of 0.072. The fifth hypothesis that customer satisfaction has no positive and significant effect on purchasing decisions. This is evidenced by the negative coefficient value (-0.228) with a t-statistic of 3.192 and a p-value of 0.001. The sixth hypothesis is that customer satisfaction can mediate the effect of service quality on purchasing decisions. This is because the coefficient value is -0.065, with a t-statistic of 2.526 and a p-value of 0.006. the seventh hypothesis that customer satisfaction cannot provide a mediating role in the effect of price on purchasing decisions. This is evidenced by the coefficient of determination of -0.028, t-statistic of 1.199, and p-value of 0.115